2023
DOI: 10.3390/buildings13061489
|View full text |Cite
|
Sign up to set email alerts
|

Satisfaction Evaluation for Underpass Green Spaces in Mountainous Cities under the Perspective of Environmental Perception

Abstract: The overpasses and the terrain under them in Chongqing, a mountainous city in China, are complex and diverse, and some spaces under the overpasses are integrated and reconstructed into the underpass green space for citizens to stroll about or have a rest. From the perspective of visitor perception, this paper constructs a perception evaluation system of the environmental characteristics of underpass green space in mountainous cities from the following five environmental perception dimensions: path organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…For the study of industrial heritage evaluation, the existing studies have mainly focused on the value of industrial heritage given by history and its intrinsic value, and its reuse value and derivation value. Among them, most scholars have focused on the dimen- The IPA method can transform the qualitative analysis of satisfaction into quantitative intuitive data, and its model is intuitive and can clearly indicate the priority of the various price indicators for the transformation needs and has been widely utilized in many fields such as transportation facilities [46], urban public spaces [6,47], industrial landscapes [36,48], heritage tourism [49], etc., and it is a tool for evaluating satisfaction. The main purpose of this paper was to construct a satisfaction evaluation system for the spatial reuse of industrial heritage and to evaluate eight industrial heritage reuse projects in the core area of Beijing, taking into account the actual feelings of the urban residential population toward the industrial heritage projects.…”
Section: Methodology For Researchmentioning
confidence: 99%
“…For the study of industrial heritage evaluation, the existing studies have mainly focused on the value of industrial heritage given by history and its intrinsic value, and its reuse value and derivation value. Among them, most scholars have focused on the dimen- The IPA method can transform the qualitative analysis of satisfaction into quantitative intuitive data, and its model is intuitive and can clearly indicate the priority of the various price indicators for the transformation needs and has been widely utilized in many fields such as transportation facilities [46], urban public spaces [6,47], industrial landscapes [36,48], heritage tourism [49], etc., and it is a tool for evaluating satisfaction. The main purpose of this paper was to construct a satisfaction evaluation system for the spatial reuse of industrial heritage and to evaluate eight industrial heritage reuse projects in the core area of Beijing, taking into account the actual feelings of the urban residential population toward the industrial heritage projects.…”
Section: Methodology For Researchmentioning
confidence: 99%
“…It reveals that regions in the Northeast, Northwest, West, and Southwest generally exhibit longer distances to green spaces, ranging from approximately 17.038 to 35.419 km. These results may be influenced by the geographical location, as studies have shown that different topography may affect the accessibility of green space [71]. Specific examples are the highlands in the West Midlands, North East, and North West, and Yorkshire and the Humber in England, with heights of around 610 m and 315 m respectively.…”
Section: Spatial Pattern Of Public Green Space Accessibility In Englandmentioning
confidence: 99%
“…Studies in environmental psychology have substantiated a significant correlation between the characteristics of public spaces and a sense of security, highlighting that those spaces inducing a sense of security facilitate the establishment of a conducive social order [2][3][4][5]. Environmental behavioral studies indicate a mutual influence between individuals and their surroundings [6][7][8][9], emphasizing that physical environments are one of the principal factors influencing people's psychological sense of security [10,11]. Universities, as relatively independent communities with distinctive characteristics, bear the crucial responsibility of talent cultivation, forming a vital part of the national social system and urban development.…”
Section: Introductionmentioning
confidence: 99%